Previous financial crises leading to stagnation: Selected case studies - Nina Dodig; Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
This paper analyses several severe financial crises observed in the history of capitalism which led to a longer period of stagnation or low growth. Comparative case studies of the Great Depression, the Latin American debt crisis of the 1980s and the Japanese crisis of the 1990s and 2000s are presented. The following questions are asked: What triggered big financial crises? Which factors intensified financial crises? And most importantly, which factors prevented the return of prosperity for a long time? The main conclusion is that stagnation after big financial crises becomes likely when the balance sheets of economic units are not quickly cleaned, when the nominal wage anchor breaks, and when there is no big and longer growth stimulus by the state. Some tentative conclusions for the subprime financial crisis and the Great Recession are drawn.
Keywords: E65; G01; N12; N15; N16; 330; financial crises; stagnation; deflation; lost decade; Great Depression; Latin American debt crisis; Japanese crisis; Great Recession